2008
DOI: 10.1086/588635
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Star Rotating at 1122 Hz and the r -Mode Instability

Abstract: We show that r-mode instabilities severely constrain the composition of a compact star rotating with a submillisecond period. In particular, the only viable astrophysical scenario for such an object, present inside the lowmass X-ray binary associated with the X-ray transient XTE J1739Ϫ285, is that it has a strangeness content. Since previous analyses indicate that hyperonic stars or stars containing a kaon condensate are not good candidates, the only remaining possibility is that such an object is either a str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
(41 reference statements)
1
25
0
Order By: Relevance
“…hyperons or deconfined quarks, is present in the inner core. In this type of stars the viscosity and thus the r-mode instability window is quite different from that of normal NSs [32]. Moreover, the evolution of the internal magnetic fields and the magnetic properties of the compact star are also expected to be different [8,33].…”
Section: The Overall Evolutionary Sequence: a General Discussionmentioning
confidence: 90%
“…hyperons or deconfined quarks, is present in the inner core. In this type of stars the viscosity and thus the r-mode instability window is quite different from that of normal NSs [32]. Moreover, the evolution of the internal magnetic fields and the magnetic properties of the compact star are also expected to be different [8,33].…”
Section: The Overall Evolutionary Sequence: a General Discussionmentioning
confidence: 90%
“…Unmasking neutron star interiors may therefore require observables based on transport properties, which could be strongly modified in the presence of color superconductivity. It has been suggested that such tests of the structure of matter at high density be based on an analysis of the cooling behavior [41][42][43][44] stability of rapidly spinning stars against r-modes [45,46]. It has turned out that these phenomena are sensitive to the details of color superconductivity in quark matter.…”
Section: Phase Transition To Quark Matter: Nucleon Dissociationmentioning
confidence: 99%
“…93 ), thus XTE J1739-285 contains the most rapidly rotating compact star discovered up to now, and the first with a submillisecond spin period (P = 0.891 ms). This discovery gives a model indipendent observational contraint to EOS dense stellar matter, and it has prompted a number of studies [100][101][102] in this direction. In one of these studies, Lavagetto et al 100 have derived the following upper limit…”
Section: Xte J1739-285mentioning
confidence: 99%